Coordinators Bridge Residents And Artists In Regional Japan: A Case Study Of The Art Project Hanarart - Horiuchi, Shiro (Penerbit Universiti Sains Malaysia (USM Press), 2017)
In the age of globalisation, the transiency of individuals has been increasing. Consequently, some regional communities face the risk of collapse and disappearance. Particularly in Japan, centralisation in and around global cities such as Tokyo has accelerated the decline of regional communities. Given this current clime, residents of regional areas would beneft from building ties with outsiders in order to keep their communities strong. Certain individuals could take on the role of coordinator, who can work to bridge the gap between the residents and outsiders. The role of the coordinator, however, is not yet clear. This study introduces a case study of the art project Hanarart ( はならぁと) which involves residents and outside artists in regional areas of Nara, Japan. Part of the art project intends to renovate and reuse the machiya buildings in Japanese traditional style, with the help of site-specifc contemporary art that will ft well with the machiya style. In the art project, outside artists prepare their artworks in the abandoned buildings, which are managed by the residents. During the frst stage of the project, residents and artists did not communicate well due to either their indiﬀerence or ignorance toward each other's interests. In the next stage, however, assigned coordinators promoted communication between the residents and artists for the sake of contemporary art. Through the process of trial and error, the project resulted in contributing to the community in a number of ways.